The Effect of Using Number Pocket Media on the Ability to Calculate Summation of Tens in Deaf Children - Aisyi, Afridha Rahadatul (research, training and philanthropy institution Natural Aceh, 2025)
There is a problem for deaf students in learning mathematics, namely that the students have not been able to understand how to calculate the summation of tens with a maximum final result of 99. This is because students tend to be passive during learning; in summation, students also sometimes make mistakes when calculating numbers with large numbers using the finger counting method, so students calculate with the wrong final result. This study aims to determine how much influence the use of number pocket media has on the ability to calculate the addition of tens in deaf children at SLBN Cicendo, Bandung City. The method used is a pre-experiment with a one-group pretest-posttest design. Data were collected through written tests. The subjects in this study were grade 12 SMALB students at SLBN Cicendo, Bandung City. The data obtained were analyzed using the Wilcoxon Signed Ranked Test. The results of this study show a significant influence between the use of number pocket media and the ability to calculate the summation of tens in deaf children at SLBN Cicendo, Bandung City.